Effect of magnesium supplementation on diaphyseal tibia fractures: a pilot study - Butala, Rajendraprasad R.; Mehta, Nrupam; Das, Sonali; Khatod, Garvit; Yadav, Atul (International Journal of Research in Orthopaedics, 2024)
Background: This study aimed to assess and compare the efficacy of magnesium supplementation in patients with long diaphyseal tibia fractures who have undergone surgical management with intramedullary interlocking nailing. Methods: In a prospective, randomized trial, thirty patients were included, with half receiving magnesium (420 mg/day) along with calcium (500 mg/day) supplementation for 3 months alongside surgical treatment. Radiological outcomes were evaluated through postoperative X-rays using the radiographic union scale for tibia fractures (RUST) scoring system at 6 and 12 weeks. Results: A significant difference was observed between the two groups. Patients receiving magnesium supplementation exhibited a notable improvement in RUST score, indicating an accelerated bone healing process. Conclusions: This study demonstrates the efficacy of magnesium supplementation in achieving superior radiologic outcomes compared to patients who did not receive such supplementation. The findings suggest that adjuvant magnesium supplementation could be a viable therapeutic option to enhance bone healing outcomes in individuals with tibia diaphyseal fractures.